Ischemic heart disease 1 - Lal, Vivek (Henry Stewart Talks, 2015)
Ischemic heart disease: overview, Blood supply to the heart (coronary circulation), Classification of cardiac ischemia, Risk factors for IHD, Pathogenesis of IHD, Clinical features of IHD, Diagnosis of IHD